Ekstraksi Gelatin Dari Tulang Ikan Layah Secara Asam Sebagai Alternatif Gelatin Halal - Kurnia, Nova; Rohmatillah, Laila Mardiana; Ilyas, M.Ali; Muhazam, Muhazam; Sumarlin, Muhamad; Fatinah, Fenny Inas (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Gelatin is a food additive that is widely used in the food, medicine and cosmetics industries. However, the source of gelatin is not only the bones and skin of halal animals such as cows and goats, but can also come from pigs. To fulfill the need for halal gelatin, it is absolutely necessary to search for other sources of halal gelatin, one of which is sea fish. This study aims to extract gelatin from the bones of sailfish as an alternative source of halal gelatin. The extraction process was carried out using an acid method, where fish bones were soaked in 3% acetic acid (1:10 w/v) for 48 hours. The resulting ossein was then washed with diluted NaOH and distilled water until the pH reached 6–7. The ossein was heated at a temperature of 80°C for 3 hours to obtain a gelatin solution. The gelatin solution was then cooled, producing a gel-like gelatin preparation with a yellowish-white color. The gelatin gel was subsequently dried in a furnace at a temperature of 40–50°C for 60 minutes. The final gelatin product was a yellow-colored powder.